An unusual and previously overlooked duck decoy in the north of Scotland - Sellers, Robin M. (Wildfowl, 2020)
Duck decoys were formerly widespread in England and Wales but, as has often been remarked, were believed to be absent from Scotland. This short communication summarises what is known about a previously overlooked decoy of an unusual circular design at Ackergill Tower in Caithness. Another decoy of recent construction in Fife and two other possible decoys in Ayrshire are referred to briefly.